Sobre ser universitário em tempos de pandemia: experiências, possibilidades e desafios da promoção de saúde mental no percurso acadêmico - Marinho, Juliana da Rosa (2022)
From the biopsychosocial perspective, mental health includes physiological, emotional, behavioral, cognitive and relational aspects of the individual. It is important to investigate this concept into a social context, understanding that different scenarios can interfere in people's states of well-being and suffering. In the present study, the university was chosen as a field of investigation since a diversity of discoveries and challenges can be observed in academic life. A current challenge refers to the COVID-19 pandemic, which since 2020 has been changing the dynamics of the academic environment to contain the spread of the virus, requiring institutions to adapt to remote teaching. Therefore, the main goal of this study was to know conceptions about mental health and experiences of being a university student during a pandemic. Six students assisted by the Student Assistance Policy of the Federal University of Santa Maria (UFSM) participated. Four weekly online conversation groups were conducted through the Google Meet platform. The meetings were recorded and transcribed. Through thematic content analysis, it was possible to reach the results that will be presented in the form of two articles: the first, "Mental health of university students: conceptions, determinant factors and care strategies", proposed to know perspectives on the meaning of mental health, as well as knowing the experiences that impacted on mental health of the university students, which the results indicated that the meanings of mental health cover a biopsychosocial perspective and consider different aspects of daily life, including social and economic elements. In addition, it was possible to understand that being a university student involves facing adverse situations, such as moving to another city, moving away from the family and establishing new bonds in an unknown context, whose adaptation brings impacts to the mental health. The second article, entitled “Experiences of being a university student during pandemic time: changes, adaptations and shared perspectives”, aimed to know experiences of university students during the pandemic, considering changes in their routines, difficulties related to the learning and training processes, as well as possible impacts of the pandemic in their mental health. The results of this article indicated that the changes caused by the COVID-19 coping strategies had a significant impact on the mental health of students, intensifying difficulties that were already experienced before the pandemic. The adoption of teaching in REDE brought insecurities in terms of academic development and the quality of training. Regarding the future, the students' expectations express optimism with the resumption of face-to-face activities, but also apprehension about what will become of the world and the community in the coming years. In general, the research was relevant for providing an environment for sharing experiences, perspectives and strategies between the students, purposing to mental health care. Furthermore, the study made it possible to understand the crossings of the pandemic in academic life, highlighting the role of the university not only in the professional training process, but also in socialization and in execution of activities that promote well-being.